PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH WORD OF MOUTH TERHADAP NIAT MENGGUNAKAN INTERNET PROVIDER BIZNET - Dewi, Ni Luh Putu Pande Cahayani; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
The phenomenon of increasing internet users in Indonesia has encouraged businesses engaged in the internet provider sector to experience very rapid development. One of the internet provider companies in Indonesia, namely Biznet. The purpose of this study is to explain the role of brand image in mediating the influence of WOM on intention to use. This research was conducted in Denpasar City with a sample of 90 respondents taken using a purposive sampling method and distributed using a Google form questionnaire with adjusted criteria and measured with 9 indicators using a Likert scale. The data analysis technique used is path analysis and sobel test. The results of this study indicate that WOM has a positive and significant effect on intention to use, WOM has a positive and significant effect on brand image, brand image has a positive and significant effect on intention to use, brand image play a significant role in mediating the influence of WOM on intention to use. The results of this study indicate that in increasing the intention to use internet services, biznet companies are expected to carry out strategies to generate positive WOM about biznet, which in turn will create a good brand image.